2015
DOI: 10.1002/tee.22182
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the suitability of rice bran oil and corn oil as alternative insulating liquids for transformers

Abstract: Increasing power demand forces the development of the high‐rated power transformers. In a transformer, petroleum‐based mineral oil is used as insulation currently. Transformer oil (TO) produces environmental and health issues because it is nonbiodegradable. The availability of petroleum products is decreasing in the present century. So it encourages researchers to find potential replacements for them. In this work, two natural ester oils (rice bran oil and corn oil) were taken up for investigation to find thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Kumar et al concluded that rice bran-based liquids indicate appropriate features such as BDV, flash point, fire point and resistivity; however thermal and other electrical characteristics are required to be improved. Palm oil has been deliberated as liquid insulation for transformers, specifically in certain states of Asia and Africa [ 143 ]. Abdelmalik made efforts to enhance the oxidation stability of palm kernel oil by chemical adjustment through the esterification reaction.…”
Section: New and Innovative Technologies For Environmentally Frienmentioning
confidence: 99%
“…Kumar et al concluded that rice bran-based liquids indicate appropriate features such as BDV, flash point, fire point and resistivity; however thermal and other electrical characteristics are required to be improved. Palm oil has been deliberated as liquid insulation for transformers, specifically in certain states of Asia and Africa [ 143 ]. Abdelmalik made efforts to enhance the oxidation stability of palm kernel oil by chemical adjustment through the esterification reaction.…”
Section: New and Innovative Technologies For Environmentally Frienmentioning
confidence: 99%
“…In fact, in the supercritical CO 2 state, the active site of the lipase was protected, the temperature tolerance of the enzyme was increased. The viscosity of rice bran oil was reduced by about 12% (Kumar, Iruthayarajan, & Bakrutheen, ). The mass transfer rate was accelerated and then it increased the esterification rate (Uddin et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Tensile strength was measured using Universal Testing Machine (UTM) according to the IEC 60554 standards. A paper strip was clamped at each end between two jaws, and an increasing load was applied causing the clamps to move apart until the strip breaks at a certain loading condition [36].…”
Section: G Prediction Of the Tensile Strength Of The Papermentioning
confidence: 99%